Morphometric Analysis of the External Aperture of the Carotid Canal in Skulls of South Indian Origin - Tewari, Siddharth; Gupta, Chandni; Palimar, Vikram; Aithal, Sanjana (Journal of Morphological Sciences, 2018)
Background and Objective The carotid canal (CC) is a bent passage in the petrous temporal bone from where the internal carotid artery (ICA) goes inside the skull. The shape, location and measurements of the CC are clinically very important in cases of skull base surgery, since the ICA has to be identified and isolated throughout its petrous course. Therefore, the present study was performed to measure and locate the CC from various important anatomical landmarks.Materials and Method The present study was conducted on 68 dry skulls of unknown gender. Various measurements and distances of the CC from various important landmarks were taken. The shape of the CC was also noted. Measurements were taken with the help of a screw-adjusted compass and of digital Vernier calipers. From the above measurements, mean and standard deviation (mean ± SD), median, range, and mode were calculated. Data analysis was done with IBM SPSS Statistics for Windows, Version 19.0 (IBM Corp, Armonk, NY, USA).Results The mean length of the CC on the right and left sides was 7.76 and 7.89 mm, respectively. The mean breadth of the CC on the right and left sides was 5.81 and 6.32 mm, respectively. The most common shape of the CC was round both on the right and left sides in 49.20% and in 53.12% of the cases.Conclusion The results of the present study will be useful in the performance of neurosurgical procedures, thereby preventing unpleasant complications.
Keywords: carotid canal; shape; neurosurgeons; base of skull; foramen magnum